Pemanfaatan Media Sosial Sebagai Alat Komunikasi Strategis Oleh Menteri Di Indonesia - anggara, reksi; Al Hamdi, Ridho; Suswanta (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
This study aims to analyze the social media accounts of Ministers in Indonesia as a means of delivering information to the public. We analyzed two Twitter accounts of Indonesian ministers who were considered to have millennial style and were active on social media, namely Erick Tohir as Minister of SOEs and Sandiaga Salahuddin Uno as Minister of Tourism and Creative Economy. The data obtained is the second Twitter post of the Minister from September 2019 to June 2023. The method in this study uses qualitative content analysis with the Nvivo 12 Plus analysis tool. The results of this study show that Erick Tohir conveyed a number of information about global cooperation, increasing dividends, and the role of SOEs for society. Meanwhile, Sandiaga Salahuddin Uno provided information on a number of bilateral relations cooperation, creative economy, and visits to various leading destinations. By looking at the number of comments, retweets, likes, and views on the average post, we conclude that Erick Tohir's communication on Twitter has a greater public response than Sandiaga Salahuddin Uno.